Changes in proliferation activity and relative distributions of lymphoid cell subpopulations in congenitally athymic nu/nu mice and Lurcher mice with spontaneous olivopontocerebellar degeneration - Cervinková, M; Mandáková, P; Síma, P (Folia microbiologica, 2006)
Changes observed in mice with congenital damage of some part of the CNS-neuroendocrine-immune regulatory system are described. nu/nu mice with congenital absence of thymus and Lurcher mice with spontaneous olivopontocerebellar degeneration displayed changes in the histoarchitecture of adrenal gland, immune organs (thymus, spleen, axillar lymph nodes) and intestine. Changes were also observed in IgM+, IgG+, CD4+ and CD8+ lymphoid cell subpopulations in the main lymphoid organs--the spleen and axillar lymph nodes and in the proliferative ability of whole lymphoid cell populations. The extreme decrease of lymphoid T-cell subpopulations in athymic nu/nu mice is the consequence of the absence of thymus, the organ of their maturation. On the other hand, a relative increase of B-cell subpopulations was found in this mouse strain. A relative decrease of CD4+ lymphocytes and a different influence of immunization on B-cell subpopulations were found in the spleen in neurodeficient Lurcher mice. The high percentage of apoptotic cells, cells in the S-phase of cell cycle and increased proliferation index in nu/nu mice suggest that the turnover and renewal of lymphoid cells in the spleen in nu/nu mice is more rapid than in control immunocompetent BALB/c mice.
Keywords: slezina; lymfocyty; Lymph Nodes; CD4-Positive T-Lymphocytes; Cell Cycle; CD8-pozitivní T-lymfocyty; olivopontocerebelární atrofie; zvířata; Mice; CD4-pozitivní T-lymfocyty; myši nahé; nadledviny; Mice, Neurologic Mutants; apoptóza; Lymphocytes; myši - mutanty neurologické; Olivopontocerebellar Atrophies; Spleen; Mice, Nude; myši; Animals; Adrenal Glands; CD8-Positive T-Lymphocytes; lymfatické uzliny; buněčný cyklus; Apoptosis